Associations of Anthropometric, Behavioral, and Social Factors on Level of Body Esteem in Peripubertal Girls. Issue 1 (January 2017) - Szamreta, Elizabeth A.; Qin, Bo; Ohman-Strickland, Pamela A.; Devine, Katie A.; Stapleton, Jerod L.; Ferrante, Jeanne M.; Bandera, Elisa V.
ABSTRACT: Objective: Lower body esteem may decrease self-esteem and lead to adverse health effects in children. This study explored the role of anthropometric, behavioral, and social factors on body esteem in peripubertal girls. Method: We evaluated associations of body esteem (measured by the Revised Body Esteem Scale) with body mass index (BMI), mother's BMI, puberty, physical activity, role models for appearance, and screen time among girls (ages 9 and 10) participating in the Jersey Girl Study (n = 120). Linear models were used to evaluate differences in body esteem scores. Results: Overweight/obese girls had a significantly lower mean body esteem score compared with underweight/healthy weight girls 14.09 (95% confidence interval [CI]: 12.53–15.27) vs. 17.17 (95% CI: 16.87–17.43). Girls who were physically active for at least 7 hours per week had a significantly higher body esteem score than those who were less active, after adjusting for BMI (17.00 [95% CI: 16.62–17.32] vs. 16.39 [95% CI: 15.82–16.86]). Girls whose mothers were overweight/obese, who had entered puberty, and who cited girls at school or females in the media as role models had lower body esteem scores, but differences disappeared after adjusting for girl's BMI. A trend of higher body esteem scores was found for girls whose mothers were role models. Conclusion: Lower BMI and higher levels of physical activity are independently associated with higher body esteem score. Having classmates or girls/women in the media as role models may detrimentally affect girls' body esteem, but having mothers as role models may have a positive effect.